Efektivitas Senam Pelvic Floor Muscle Exercise Untuk Menurunkan Frekuensi Bak Pada Lansia dengan Gangguan Eliminasi Urine: Studi Kasus - Dian Ayu Maulida; Ema Waliyanti (Jurnal Ners, 2026)
Urinary elimination disorders are a common problem experienced by the elderly due to physiological changes in the urinary system, particularly decreased pelvic floor muscle strength. This condition can reduce the comfort and quality of life of the elderly if not properly managed. This study aims to determine the effectiveness of Kegel exercises for urinary elimination disorders in the elderly. The research method used was descriptive with a case study approach in one 70-year-old woman who experienced increased urinary frequency. Data collection was carried out through interviews, observations, and recording of urinary elimination sheets for four weeks. The intervention provided was Kegel exercises performed once per day for four weeks. The results showed changes towards improving urinary elimination patterns, characterized by a decrease in urinary frequency before the intervention to 20 times/day and after the intervention to 8 times/day. These results indicate that Kegel exercises can be used as a simple, safe, and applicable non-pharmacological nursing intervention for the elderly with urinary elimination disorders. Consistency and frequency of exercise are important factors in increasing the effectiveness of the intervention.